Procédures référentielles indexicales, relations rhétoriques et structuration du discours - Francis Cornish (Discours)
This article argues that it is not the indexical expression in and of itself (whether a 3rd person pronoun, etc.) which fulfils the indexical referring function, whether it is deixis, “anadeixis” or anaphora; but rather the indexical procedure chosen by the speaker/writer as such. It is this procedure which is realised by the indexical in question, within the host predication.    In this respect, we seek to distinguish, following Ehlich (1982), the indexical procedures corresponding to deixis, anadeixis and anaphora, and to make precise their respective discourse functions. Each of these procedures is specialised in realising various types of integrative structuring of the discourse which can be associated with a given text, via an appropriate context. As for anaphora, this procedure is closely bound up with the rhetorical or coherence relations which similarly structure a discourse. It even serves to implement the rhetorical relation connecting two units satisfying the semantic and pragmatic conditions which justify the application to them of the relation at issue.